The Nigerian Blue Economy: Opportunities and Difficulties for Economic Development - Stephen Adi Odey (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2023)
The agricultural sector of the Nigerian economy played a pivotal role in Nigeria's economic growth prior to the oil boom of the 1970s. The inherent volatility of the global oil market, upon which the Nigerian economy heavily relies, has been repeatedly questioned in recent times. There is a growing call to diversify into other sectors, with the blue economy emerging as a potential driver of economic growth—a subject of considerable debate in both developed and less developed countries. This study, therefore, centers on the blue economy and its impact on the economic growth of the Niger Delta region and the Nigerian state. The findings reveal that the blue economy contributes to Employment, Job Creation, and Poverty Eradication, while also addressing challenges such as Ending Hunger, Securing Food, Promoting Physiological condition and Sustainable Fisheries, Sustainable Energy and Natural Resources, Innovative Industries, and fostering People, Culture, Communities, and Societies. However, the study highlights various challenges facing the blue economy, including sea piracy, illegal arms trafficking, terrorism, the destruction of maritime ecosystems, pollution, global climate change, and the overreliance on oil and gas, particularly among the Niger Delta states. The survival of the blue economy is intricately linked to addressing these challenges. To address these issues, the study recommends comprehensive policy reforms to enhance the blue economy. Additionally, it suggests the employment of youths as coast guards along waterways and deep-sea areas to mitigate sea piracy and related problems. The establishment of maritime education and skills training centers/schools and the formulation of policies that extend beyond the oil sector are also recommended for each Niger Delta state and the Nigerian nation.